1980
DOI: 10.1038/sc.1980.39
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and urodynamic assessment of alpha-adrenolytic therapy in patients with neurogenic bladder function

Abstract: Abstract. The efficacy of alpha-adrenolytic treatment with oral phenoxybenzamine chloride (40 mg per day during three to four months) has been assessed both clinically and urodynamically among 249 patients with neurogenic bladder function. The results were significantly better in patients with autonomous (n = 95) than in the ones with automatic (n = 154) bladders (urethral sphincter spasticity and detrusor sphincter dyssynergia dominating the clinical picture in the latter event). A further striking difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

1982
1982
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 46 publications
0
17
0
2
Order By: Relevance
“…absence of emission, a known side effect of the alpha blocking drugs on the seminal tract (Hachen, 1980). The duration of treatment ranged from 6-12 months, with an average time of 9· 5 months.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…absence of emission, a known side effect of the alpha blocking drugs on the seminal tract (Hachen, 1980). The duration of treatment ranged from 6-12 months, with an average time of 9· 5 months.…”
Section: Resultsmentioning
confidence: 99%
“…Several authors (Hachen, 1980;Scott, 1978) report better results in lower motor neurone lesions, probably due to the urethral denervation hypersensitivity, while others (Mobley, 1976) report better results in reflex bladders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly Olsson and colleagues (1977) reported improved voiding as judged by flow measurements in six patients out of II with upper motor neurone lesions. Conversely, Hachen (1980) reported the value of phenoxybenzamine in improving voiding in patients with auto nomous bladders but with no effect in those with automatic bladders. In vitro studies of human detrusor strips have shown that phentolamine resulted in the inhibition of an electrically evoked response.…”
Section: Discussionmentioning
confidence: 99%